PENGARUH KOMITMEN ORGANISASI, AKUNTABILITAS PUBLIK, PARTISIPASI PENYUSUNAN ANGGARAN, DAN KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA MANAJERIAL (Studi pada Organisasi Perangkat Daerah Kota Surakarta) - Oktaviana, Adhelia Widyan; Suharno, Suharno; Widarno, Bambang (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
This study was conducted to determine and examine the influence of organizational commitment, public accountability, budgetary participation and clarity of budget targets significantly to managerial performance. This study uses a survey method that was conducted at the Organisasi Perangkat Daerah Kota Surakarta. The data source is primary data. The technique of collecting data using a questionnaire. The sampling technique used purposive sampling method with the number of respondents in this study are 92 people. The data analysis technique uses multiple linear regression analysis. The results of this study indicate that the variable organizational commitment, public accountability and budgetary participation partially influence managerial performance, while the variable budget goal clarity partially has no effect on managerial performance. Simultaneously, variable organizational commitment, public accountability and budgetary participation as well as clarity of budget targets have an influence on managerial performance.